Real-World Recurrence Rates and Economic Burden in Patients with Resected Early-Stage Melanoma - Sekwon Jang; Tayla Poretta; Tarun Bhagnani; Qing Harshaw; Matthew Burke; Sumati Rao (Adis, Springer Healthcare, 2020)
Abstract Introduction Real-world data on recurrence and economic burden in patients with resected early-stage melanoma are limited. The objective of this study was to assess real-world recurrence rates, risk factors for recurrence, and costs of recurrence in patients with resected stage IIB, IIC, or IIIA melanoma in the USA. Methods This retrospective analysis included patients with resected stage IIB, IIC, or IIIA melanoma (American Joint Committee on Cancer staging manual, seventh edition) in the Surveillance, Epidemiology, and End Results (SEER) program-Medicare database of the National Cancer Institute. Recurrence rates and healthcare costs (2018 USD) after recurrence were assessed. Results Two-year recurrence rates for stages IIB, IIC, and IIIA melanoma were 29, 44, and 46%, respectively. In patients with stage IIB or IIC disease, the odds of recurrence were significantly higher in those aged > 75 years [odds ratio (OR) 1.853, 95% confidence interval (CI) 1.416, 2.425], with ulceration (OR 1.771; 95% CI 1.293, 2.425), or with a higher Charlson Comorbidity Index (OR 1.244; 95% CI 1.129, 1.372); however, the odds of recurrence were significantly lower in those with T3 staging (OR 0.522; 95% CI  0.393, 0.695). In those with stage IIIA melanoma, superficial spreading was associated with significantly lower odds of recurrence (OR 0.178; 95% CI 0.053, 0.601). Following recurrence, mean healthcare costs at 1 year were $31,870 for patients with stage IIB or IIC melanoma and $29,224 for those with stage IIIA melanoma. Conclusion The SEER data show that a substantial proportion of adults with early-stage melanoma experience a recurrence within 2 years following resection, resulting in a significant economic burden to the US healthcare system. Dermatologists can distinguish patients with resected early-stage melanoma who are at a high risk for recurrence and consider referrals to medical oncologists for approved adjuvant therapy or enrollment in clinical trials after surgical resection to reduce the recurrence of melanoma.